1997
DOI: 10.1175/1520-0485(1997)027<1181:srambr>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Resuspension and Mixing by Resonantly Generated Internal Solitary Waves

Abstract: The observation of internal solitary waves (ISWs) propagating upstream along a strongly stratified bottom layer on the California shelf is reported. An increased concentration of particulates in the water column accompanies the passage of these ISW packets. The estimated local Richardson number in the bottom vicinity is around 1/4, and a vertical coefficient of eddy diffusivity of order 10 Ϫ2 m 2 s Ϫ1 is associated with the upstream propagating leading ISW. The leading ISW gave rise to reversed flow in an 8-m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
152
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(170 citation statements)
references
References 25 publications
16
152
2
Order By: Relevance
“…Puig et al (2001) also observed a correlation of increased bottom concentrations with decreased temperatures at the inertial period, and ascribed those changes to resuspension of bottom material by the breaking of nearinertial internal waves as they progressed up the continental shelf (Cacchione and Drake 1986). There have also been observations of the resuspension of bottom material by solitary internal waves generated by currents impinging on the continental shelf (Bogucki et al 1997, Johnson et al 2001, and similar processes may occur in Lake Michigan. These solitary waves typically have periods of several minutes, so they are unlikely to be detected by hourly measurements.…”
Section: Discussionsupporting
confidence: 89%
“…Puig et al (2001) also observed a correlation of increased bottom concentrations with decreased temperatures at the inertial period, and ascribed those changes to resuspension of bottom material by the breaking of nearinertial internal waves as they progressed up the continental shelf (Cacchione and Drake 1986). There have also been observations of the resuspension of bottom material by solitary internal waves generated by currents impinging on the continental shelf (Bogucki et al 1997, Johnson et al 2001, and similar processes may occur in Lake Michigan. These solitary waves typically have periods of several minutes, so they are unlikely to be detected by hourly measurements.…”
Section: Discussionsupporting
confidence: 89%
“…They are thus expected to provide potential for significant material mixing across the BBL and in extreme cases, sediment resuspension. ISW-induced mixing and resuspension was observed on the California Shelf (Bogucki et al, 1997), where the wave passage was accompanied by an increased concentration of particulates in the water column. Since the near-bottom current speed was much lower than the traditionally expected threshold value for sediment resuspension, this observation suggests that the ISW and ISW-induced unsteady flow can potentially be responsible for both mixing and resuspension.…”
Section: Introductionsupporting
confidence: 56%
“…Internal solitary-like waves (henceforth ISWs) are a commonly observed feature of many natural bodies of water including both the deep and coastal oceans as well as large lakes (Bogucki et al, 1997;Hosegood and van Haren, 2004;Bogucki et al, 2005;Carter et al, 2005;Moum and Smyth, 2006;Moum et al, 2007). Being both nonhydrostatic and finite amplitude, naturally occurring ISWs cannot be accurately represented by hydrostatic numerical models (including all models presently used for global ocean dynamics and climate simulations) or linear wave theories.…”
Section: Introductionmentioning
confidence: 87%